2021
DOI: 10.1002/jsfa.11680
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up redistribution of biomass optimizes energy allocation, water use and yield formation in dryland wheat improvement

Abstract: BACKGROUND Modern wheat cultivars have been developed having distinct advantages in many aspects under drought stress, such as plasticity in biomass allocation and root system architecture. A better understanding of the biomass allocation mechanisms that enable modern wheat to achieve higher yields and yield‐based water use efficiency (WUEg) is essential for implementing best management strategies and identifying phenotypic traits for cultivar improvement. We systematically investigated the biomass allocation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
(164 reference statements)
0
9
0
4
Order By: Relevance
“…Osmotic stress often causes a deterioration of plant monovalent ion balance [ 40 ], but for OA10, no obvious ion imbalance was detected ( Figure 2 , Figure 3 , Figure 4 and Figure 5 ). Studies suggest that modern hexaploid wheat genotypes have shifted their biomass from below ground to above ground to optimize water use [ 41 ], however, this trait was not investigated as part of this study. Moreover, as ABA can prevent transpiration and thereby also decrease Na + movement from the root to the stem [ 42 ], it would be a feature to look for in future studies to understand better the patterns that appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic stress often causes a deterioration of plant monovalent ion balance [ 40 ], but for OA10, no obvious ion imbalance was detected ( Figure 2 , Figure 3 , Figure 4 and Figure 5 ). Studies suggest that modern hexaploid wheat genotypes have shifted their biomass from below ground to above ground to optimize water use [ 41 ], however, this trait was not investigated as part of this study. Moreover, as ABA can prevent transpiration and thereby also decrease Na + movement from the root to the stem [ 42 ], it would be a feature to look for in future studies to understand better the patterns that appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Drought is considered the most severe abiotic stress affecting plant growth and limiting crop yield throughout the domestication process from primitive to modern hexaploid genotypes. Therefore, it is becoming more and more important to develop drought‐resistant varieties (Bruce et al, 2002; Kitchen et al, 1999; Li, Ma, Guo, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that an overall increase in root biomass does not imply increased water uptake, which should be reduced in crop breeding (Zhang et al, 1999; Reynolds et al, 2006; Aziz et al, 2016). Reduced root mass may reduce root growth redundancy and facilitate redistribution, transferring more dry matter from roots to shoots (Siddique et al, 1990; Zhang et al, 1999; Song et al, 2009; Li, Ma, Guo, et al, 2022). The effect of reducing root size under drought conditions on wheat grain yield has been extensively investigated, but conclusions remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations